Distribution of Size-Fractionated Chlorophyll a and Picocyanobacteria in Coastal Waters of Northwest and Southeast Peninsular Malaysia - Joon Hai, Lim; Choon Weng, Lee; Xiaoju, Pan; Yi You, Wong; Chui Wei, Bong; Kumaran, Narayanan; Edmund Ui Hang, Sim; Tung Yuan, Ho; George TF, Wong (Springer Nature, 2025)
Sampling was at two coastal sites in Peninsular Malaysia; Yan (along Straits of Malacca during Northeast and intermonsoon) and Kuala Rompin (KR, facing the South China Sea during Southwest monsoon). Despite temporal offsets in sampling, distinct spatial patterns of nutrients and picocyanobacteria were observed. Nutrient variability at Yan was influenced by freshwater discharge, and there was a predominance of NH4 (51 ± 25% of dissolved inorganic nitrogen). At KR, conditions were more stable and less eutrophic, and NO2 + NO3 predominated (53 ± 25% of dissolved inorganic nitrogen). Although the > 20 μm Chl a fraction was predominant, only Prochlorococcus (from 70 to 1.2 × 104 cells mL–1) correlated with the < 2 μm Chl a fraction at Yan (R2 = 0.221, p < 0.01) whereas at KR, only Synechococcus (from 100 to 8.5 × 104 cells mL–1) correlated with the < 2 μm Chl a fraction (R2 = 0.135, p < 0.05). Redundancy Analysis (RDA) revealed that Synechococcus was associated with higher salinity and lower temperature, DO, PO₄ and NO₂+NO₃ while Prochlorococcus occupied a distinct niche along a separate RDA axis. This baseline study is a novel investigation into picocyanobacterial dynamics for Malaysia, and reveals their niche differentiation in tropical coastal systems.